A simple method enabling efficient quantitative analysis of the Portevin–Le Chatelier band characteristics. (1st January 2023) - Xu, Jianbin; Liu, Lei; Hopperstad, Odd Sture; Holmedal, Bjørn; Mánik, Tomáš; Marthinsen, Knut
Abstract: Localized deformation bands are often observed in materials exhibiting the Portevin–Le Chatelier (PLC) effect. However, efficient quantitative analysis of PLC bands remains challenging. A novel method is thus proposed in this work, where a multi-strain-jump function is introduced to capture the experimentally obtained staircase-like strain profile from digital image correlation (DIC). This approach is simple to implement and allows for: (i) automatically extracting the band strain throughout the test, which can be used to further evaluate the band velocity, and (ii) linking band characteristics with the corresponding local material properties. The efficiency of the method is demonstrated by analysing the band characteristics for different strain rates and temperatures. The results reveal that the relative band velocity is proportional to the work hardening rate, i.e., v b / v g ∝ Θ, for the continuously propagating type A bands. Graphical abstract: Image, graphical abstract